Synergism of Antioxidant Activity Combination of Buas-Buas (Premnaserratifolia Linn.), Meniran (Phyllanthusniruri L.), Secang (Caesalpiniasappan) and Roselle (Hibiscus sabdarifa) Extracts - Isnindar Isnindar; Sri Luliana (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Buas-buas, meniran, secang, and rosella have biological and pharmacological activities as antioxidants. The combination of the four plants is expected to provide a more potent synergistic effect on antioxidant activity. The purpose of this study was to analyze the total phenol content, total flavonoids, and antioxidant effects before and after combination. The combination of extracts, buas-buas, meniran, secang, and rosella which are used in sequence is (1: 1: 1/2: 1/2), (1: 2: 1/2: 1/2), and (2: 1 : 1/2: 1/2). Plants used in the form of simplicia was extracted by maceration method. Radical capture activity uses DPPH and IC50 values are determined. Determination of total phenol is expressed equivalent to gallic acid. Total flavonoids are expressed as quercetin equivalents. The phenol and flavonoid content obtained are then correlated with antiradical activity. The results showed that the best IC50 values were in the combination of ratios (1: 1: 1/2: 1/2) that is (11.0 µg / mL), then (1: 2: 1/2: 1/2) which was 13.3 µg / mL, and (2: 1: 1/2: 1/2) which is 19.4 µg / mL. The highest total phenolic and flavonoid content in the ratio (1: 2: 1/2: 1/2) is 33.57% w/w EAG and 74.00% w/w EQ. Correlation analysis between IC50 values with total phenolic and flavonoid contents showed a positive correlation with R2 values of 0.8236 and 0.0102 with positive slope. Thus, it can be concluded that the total phenol content influences free radical scavenging activity by 82.36%, while the effect of total flavonoid content was only 1.02%.